Are the functionality of website and logistics systems driving e-customer satisfaction in South Africa - Prof S. Perks; Tariro Shumba (The Retail and Marketing Review)
Although online shopping has increased globally, South Africa (SA) still lags behind developed countries in the adoption of online shopping. This study aimed at determining which online shopping system functionalities drive e-customer satisfaction in SA. Specifically, the study examined if website and logistics system functionality can predict e-customer satisfaction. A positivistic quantitative approach was adopted to collect data using a structured self-administered questionnaire. A final usable sample of 237 South African online shoppers older than 18 years was obtained in the online survey. Convenience and snowball sampling was used to collect data and analysed using descriptive and inferential statistics. The study concludes that only website system functionality augments e-customer satisfaction, while logistics system functionality is an element of the shopping experience that falls outside the scope of this article. Online shops should thus carefully plan the design of their website to ensure it is functional and meets or exceeds customers’ expectations. The website must perform in the manner for which it is designed and guide customers to product categories with relative ease and enable quick product image downloads. The website landing page should provide all product and delivery information, product availability status and stock-out conditions.